Postscript: How We Learn Is How We SEE. Issue 3 (August 2020) - Morrison, Emily A.; Kowalski, Rita
The Problem: Workplace learning is even more important today as organizations face complex, rapid, and unprecedented change. Reflection is critical to learning; yet, it is too often rote, haphazard, or assumed to happen, limiting an organization's ability to adapt. The Solution: HRD scholar-practitioners need to (re)examine how they and their organizations reflect. By engaging in an ongoing practice of reflexivity, they can become more aware of how their perspectives affect not only what they see, but also what they learn and vice versa. The Stakeholders: HRD scholar-practitioners, including researchers, faculty, consultants, managers, students, and all who care about workplace learning and reflective practice, will benefit by reflecting on how they can develop individual and collective capacity.